THE INFLUENCE OF MARKETING INSTRUMENTS IS ON DESCRIPTIONS OF CONSUMER BEHAVIOR - Жук, Оксана (SWorldJournal, 2024)
Successful and developed companies annually invest many millions of dollars in the study of consumer behavior and consciousness, in the process of making a purchase decision, inventing new ways to manipulate consumer behavior. This is made possible by th